A Lost Generation? Education Decisions and Employment Outcomes during the US Housing Boom-Bust Cycle of the 2000s - Laeven, Luc; Popov, Alexander (American Economic Review, 2016)
We exploit regional variations in U.S. house price fluctuations during the boom-bust cycle of the 2000s to study the impact of the housing cycle on young Americans' choices related to education and employment. We find that in MSAs which experienced large increases in house prices between 2001 and 2006, young adults were substantially more likely to forego a higher education and join the workforce, lowering skill formation. During the bust years, the young, especially those without higher education, were more likely to be unemployed in areas which experienced higher declines in house prices.